2000
DOI: 10.1074/jbc.m003192200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocytes Contribute to Soluble CD14 Production, and CD14 Expression Is Differentially Regulated in Hepatocytes and Monocytes

Abstract: CD14 presents as a glycosylphosphatidylinositollinked membrane protein on the surface of monocytes/ macrophages and as a soluble protein in the serum. Our previous studies have shown that an 80-kilobase pair (kb) genomic DNA fragment containing the human CD14 gene is sufficient to direct CD14 expression in a monocyte-specific manner in transgenic mice. In addition, we discovered that human CD14 is highly expressed in hepatocytes. Here, we report the generation of transgenic mice with either a 24-or 33-kb human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 51 publications
2
63
0
2
Order By: Relevance
“…sCD14 is produced not only by monocytes but also by hepatocytes, and the liver has been claimed to constitute one of the major sources of sCD14 (25 ). Here we describe that both insulin resistance and circulating sCD14 concentrations were associated with serum ALT in a population of apparently healthy individuals.…”
mentioning
confidence: 78%
“…sCD14 is produced not only by monocytes but also by hepatocytes, and the liver has been claimed to constitute one of the major sources of sCD14 (25 ). Here we describe that both insulin resistance and circulating sCD14 concentrations were associated with serum ALT in a population of apparently healthy individuals.…”
mentioning
confidence: 78%
“…In humans, the main source of sCD14 is liver hepatocytes [15], which produce substantial amounts (1-2 lg/mL on average) of soluble protein. Fig.…”
Section: Generation Of Transgenic Micementioning
confidence: 99%
“…Additionally, a soluble form of the CD14 molecule (sCD14) may be found in serum due to shedding from cell membranes. It has also been suggested that hepatocytes, in particular, could be a source of sCD14 production [3,4]. The CD14 gene is localized on chromosome 5q31.1, and a C-to-T transition polymorphism at position -159 in the promoter region of the CD14 gene may influence the sCD14 level [5].…”
Section: Introductionmentioning
confidence: 99%